Systems integration implications of component reuse. Issue 6 (9th August 2022) - Grumbach, Joshua Logan; Thomas, Lawrence Dale
Abstract: Component and subsystem reuse has been an important tool in controlling the cost and schedule requirements of developing new aerospace systems. Although the mere utilization of component reuse cannot be shown to influence system integration success significantly, previous research has shown that interactions between reuse and other integration principles do significantly influence integration success. The research described in this paper leverages historical system data to characterize these interactions and assess the influence of these interactions on integration success. This research identifies four characterizations of interactions between reuse and the other principles that significantly influence system integration success when component reuse is included in the system design.